Histopathological study of perilesional skin in patients diagnosed with nonmelanoma skin cancer. (20th July 2015) - Apalla, Z.; Calzavara‐Pinton, P.; Lallas, A.; Argenziano, G.; Kyrgidis, A.; Crotti, S.; Facchetti, F.; Monari, P.; Gualdi, G.
Summary: Background: Epidemiological and clinical data suggest that actinic damage to the skin is an important predictor of skin carcinogenesis. Aim: To investigate the association of squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) with sun‐damage alterations seen by histopathology. Method: In the current prospective study, perilesional skin of SCC or BCC lesions was evaluated for presence of alterations associated with chronic photodamage. Presence of scarring, perineural/perivascular invasion, haemorrhage/haemorrhagic crust, ulceration/erosion and margin involvement were also assessed. Result: Of 6038 included lesions, 4523 (74.9%) were BCCs and 1515 (25.1%) were SCCs. Presence of actinic damage was five times more frequent in SCC than in BCC (OR = 5.29, 95% CI 4.44–6.00, P < 0.001), and diagnosis of SCC was twice as common in photo‐exposed than nonphoto‐exposed body sites (OR = 2.34, 95% CI 2.03–2.70, P < 0.001). There were twofold higher odds for actinic damage in SCC compared with Bowen disease (OR = 2.015, 95% CI 1.55–2.61, P < 0.001). Assessing the different BCC histological subtypes, we found that nodular BCC had at least twofold higher odds (OR = 2.63, 95% CI 2.09–3.32), infiltrative BCC had 48% higher odds (OR = 1.487, 95% CI 1.18–1.87) and basosquamous BCC had fourfold higher odds (OR = 4.10, 95% CI 3.01–5.57) of having actinic damage compared with superficial BCC. Conclusions: Histological verification of ultraviolet‐associated alterations in the perilesional skin in patients with NMSC in our study confirms the aetiopathogenic link between sun exposure and epithelial carcinogenesis on a histopathological basis. This correlation was stronger for SCCs than for BCCs.